The Study Redox Catalytic of KARES@PdNPs Using Formic Acid - Busroni, Busroni; Yudi Aris Sulistyo; Donatus Setiawan Purwo Handoko; Novita Andarini (Indonesian Chimica Letters, 2024)
This study aims to synthesize Calixresorcine material and KARES@PdNPs nanoparticles as catalysts to support the synthesis of PdNP nanoparticles. The process of interaction of the hydroxy groups with palladium (II) cations led to a significant decrease and increase in the quality of the nanoparticles and could increase the specific quality of KARES@PdNPs nanoparticles and increase the catalytic activity of KARES@PdNPs with a very high number of PdNPs. Thus, the KARES@PdNPs is very suitable and shows a very efficient catalytic ability in the redox reaction process.